Fluid practices and functions linked with traditional cuisine Busri in Sindh- Pakistan - Kousar, Umbreen; Khoso, Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2022)
Some foods play essential symbolic functions in certain practices in some communities. Busri – a Sindhi traditional cuisine in Sindh, Pakistan, has various unexplored functions in the social, cultural, and religious contexts in which it has been served. The article uses archival data collected from the Sindhi Adbi Board. The paper applies Robert Merton’s concept of manifest and latent functions to understand busri as a social and cultural phenomenon and further analyses whether busri has performed latent functions to perform any role to bring a change to Sindhi communities (as Merton had asserted). Busri has reportedly manifest social, cultural, religious, and health-related functions. However, the article argues that the scale of these functions is neither large nor mandatory. The article also argues that busri lacked latent functions to serve the Sindhi community’s unintended purposes. Therefore, once it remained a regular part of Sindhi communities’ social, cultural, religious, and health-related practices, it has been disappearing in the rural areas of Sindh, where it is considered a delicacy of the rich class.